Seven new species of Enna (Araneae: Trechaleidae) from Central and South America - Da Silva, Estevam L. Cruz; Lise, Arno A. (Zootaxa, 2011)
Seven new species of the spider genus Enna O. Pickard-Cambridge, 1897 from Central and South America are described and illustrated for the first time: Enna carinata sp. nov. (male, Panama), E. triste sp. nov. (male, Venezuela), E. caricoi sp. nov. (male, Colombia), E. venezuelana sp. nov. (female, Venezuela), E. silvae sp. nov. (female, Peru), E. frijoles sp. nov. (female, Panama) and E. zurqui sp. nov. (female, Costa Rica). A new record of Enna estebanensis (Simon, 1898) is reported from Ecuador.